House at 115 N. Green Street that was formerly a log school, 1984. - Rogers, Tom (Forsyth County Public Library, 1984)
TCS 11-1-84 p.26.
House at 115 N. Green Street that was formerly a log school, 1984.
Keywords: Forsyth County (N.C.) -- History -- Sources; Digital Forsyth; Forsyth County (N.C.) -- History -- Pictorial works